Macro and micro investigation of gravel content on simple shear behavior of sand-gravel mixture. (10th October 2019) - Xu, Dong-Sheng; Tang, Jian-Yi; Zou, Yan; Rui, Rui; Liu, Hua-Bei
Highlight: GC effect on shear behavior of SGM is investigated at macro- and micro-scales. Large-scale simple shear tests on SGM were conducted and simulated by DEM. The micro-mechanism of GC effect was studied based on DEM simulations. GC affects shear behavior of SGM though friction mobilization at micro-scale. Abstract: The gravel content (GC) may influence the mechanical properties of sand-gravel mixture (SGM) used in earth structures and may compromise the stability of such structures. The purpose of this paper is to present a macro and micro study on the effect of GC on simple shear behavior of SGM using experimental and numerical approaches. Firstly a series of large-scale simple shear tests on SGM with different gravel contents under different normal stresses were conducted. The test results demonstrate that GC affects the shear strength and friction angle of SGM according to the change of void ratio at macro-scale. The variations of dilatancy and initial modulus with GC were also discussed. Then a 3D discrete element model was established for numerical simulations, in which the grading distributions of particles had similar shapes with the simple shear tests, but the particle size was 5 times scaled. The Herts-Mindlin model was used for contact, and the rolling resistance was taken into account. The numerical results showed a fairly good agreement with the experimental results. After that the micro mechanism of gravel content effect was investigated according to the analysis of micro force chain topology and contact force distributions. In summary, the experimental and numerical investigations provide valuable insights into the gravel content effect of SGM at both macro- and micro- scales.